2020
DOI: 10.1088/1361-6463/abaf7b
|View full text |Cite
|
Sign up to set email alerts
|

Polarity control and fabrication of lateral polarity structures of III-nitride thin films and devices: progress and prospects

Abstract: Due to their non-centrosymmetric crystal orientation, wurtzite III-nitride crystals have two distinct orientations, i.e. III-polar and N-polar along the c-axis. Extensive effort has been devoted to polarity control and the characterization of III-nitride thin films. Both III-polar and N-polar films possess some unique features. By taking full advantage of both III and N-polar domains in a single structure, a lateral polarity structure (LPS), where III-polar and N-polar domains are grown side-by-side simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 145 publications
0
9
0
Order By: Relevance
“…Highperformance UV-C PDs can also revolutionize the medical diagnosis, chemical/biological threat detection, sterilization process, etc. [5][6][7] Many efforts have been made to develop UV-C detectors using epitaxially grown group III-nitrides and oxide films [7][8][9]. These materials are stable at high temperatures and possess wide bandgap characteristics with wavelength tunability in the UV wavelength regime (200-400 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Highperformance UV-C PDs can also revolutionize the medical diagnosis, chemical/biological threat detection, sterilization process, etc. [5][6][7] Many efforts have been made to develop UV-C detectors using epitaxially grown group III-nitrides and oxide films [7][8][9]. These materials are stable at high temperatures and possess wide bandgap characteristics with wavelength tunability in the UV wavelength regime (200-400 nm).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, III-nitride structures with lateral periodic metal-polar and N-polar domains have been used for second harmonic generation in compact tunable optical sources, for UV light emitting diodes (LED) with increased internal quantum efficiency, for Schottky barrier diodes with reduced on-resistance, and for novel threeterminal devices. [5][6][7][8][9][10] Notably, N-polar high electron mobility transistors (HEMTs) have emerged as very promising to expand device designs by offering improved scalability, reduced resistance of ohmic contacts, better confinement of the two-dimensional electron gas (2DEG), and better dynamic performance compared to metal-polar devices. [11][12][13][14][15] It has been shown that by varying growth temperature, V/III ratio, and surface pretreatment, either N-polar, metal-polar, or a mixed-polarity III-nitride layers can be realized.…”
Section: Introductionmentioning
confidence: 99%
“…High-performance UV-C PDs can also revolutionize the medical diagnosis, chemical/biological threat detection, sterilization process, etc. [5][6][7] Many efforts have been made to develop UV-C detectors using epitaxially grown group III-nitrides and oxide films [7][8][9]. These materials are stable at high temperatures and possess wide bandgap characteristics with wavelength tunability in the UV wavelength regime (200 ~ 400 nm).…”
Section: Introductionmentioning
confidence: 99%